Effect of bitter melon and garlic on blood glucose level and blood cholesterol level in rats in diabetic condition (Research in Agriculture Livestock and Fisheries, 2018)
The aim of this research was designed to investigate the single and combine effect of bitter melon and garlic on blood glucose level and blood cholesterol level in rats in diabetic condition. In this study 60 rats (12 normal rats and 48 alloxan induced diabetic rats) was used for trials. The rats were divided into 5 groups for each trial, each containing 12 individuals as follows: First group was normal control (A), Second group was diabetic control (B), third group was alloxan with bitter melon treated (C). Group D was alloxan and Garlic treated and Group E was alloxan, bitter melon, garlic treated. Then alloxan injection was injected at the dose rate of 100mg/kg body weight intraperitoneally to each rate to induce diabetes in groups B, C, D and E. On 10th day blood glucose level, blood cholesterol level and the body weights were measured for the first time to ensure diabetic induction as well as hypercholesterolemia. Then all the rats of that group were kept for more 21 days for the treatment of hyperglycemia and hypercholesterolemia. During that period on Day 0, 7, 14 and 21st the body weight, blood cholesterol level and blood glucose level were measured. Aqueous extract of bitter melon and garlic were fed at a dose rate of 300mg/kg and 500 mg/kg body weight for 21 days in group C and D respectively and combine in group E. The blood sugar level and blood cholesterol level were reduced in bitter melon, garlic & combine treatment groups compare with untreated group. From these findings it is concluded that the combination of bitter melon and garlic can be used as anti-hyperglycemic and anti- hypercholesterolemic agent.Res. Agric., Livest. Fish.5(3): 359-363, December 2018